Occupational accidents among rice farmers in Northern Vietnam - My Ha Nguyen; Toan Van Ngo; Anh Quynh Tran; Linh Gia Vu; Nga Thu Phan; Son Truong Pham; Duc Minh Nguyen; Hai Minh Vu (Scientific Reports)
Abstract This study investigated the rate of agricultural occupational accidents among rice farmers in rural Northern Vietnam and identified factors associated with these accidents. A cross-sectional study was conducted on rice farmers in rural Thai Binh province, Northern Vietnam. A multi-stage random sampling method was used to select 1,171 rice farmers from six communes. Data were collected through structured interviews at the participants’ homes using a pilot-tested questionnaire that gathered information on occupational accidents in the previous six months, including their causes, frequency, and related injuries. Logistic regression analysis was performed to assess the factors associated with occupational accidents, considering variables such as age, gender, alcohol consumption, daily exercise, and working hours. Model fit was evaluated using goodness-of-fit tests, and significant variables were identified based on a p-value of < 0.05. Of the 1,171 rice farmers, 17.5% reported experiencing at least one occupational accident in the preceding six months. Sharp objects were the leading cause of accidents (46.3%), followed by falls (37.1%). Additionally, 41.0% of farmers who experienced accidents reported having three or more incidents in the past six months. The multivariate logistic regression analysis revealed that the likelihood of occupational accidents was significantly associated with increasing age, female gender, lack of daily exercise, alcohol consumption, and longer working hours. The final model showed good fit, with these variables demonstrating independent contributions to the accident risk. This study found a significant prevalence of occupational accidents among rice farmers in Northern Vietnam. Factors such as age, gender, exercise habits, alcohol use, and working hours were associated with higher accident risk. Future research should focus on exploring the knowledge, attitudes, and practices of farmers regarding accident prevention, and interventions should be developed to address these risk factors and improve safety in rice cultivation.